Feasibility of Central Bank digital currency for blockchain-based zakat in Indonesia - Zulkifri, Zulkifri; Adam Sa'ad, Auwal; Salina, Kassim; Anwar Hasan, Abdullah Othman (Springer, 2022)
Distrust to zakat institutions is one of the causes zakat funds not reaching the potential amount in Indonesia. Blockchain technology, with its capability of tracing, can provide transparency information. The Blockchain-based Zakat can potentially overcome distrust issues to zakat institutions. However, the legal status of cryptocurrency is still skeptical. This study aims to see the feasibility of CBDC can be implemented in blockchain-based Zakat in Indonesia. The method used in this research is the qualitative method. An extensive literature review method was utilized to identify and analyze the relevant literature in order to propose the model. This study suggests Blockchain-based Zakat with the use of CBDC and BAZNAS as the zakat agencies.